Characterization of diesel-degrading enzymes from Acinetobacter sp. strain DRY12 (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2013)
The purpose of this work was to elucidate the type of metabolic pathway involved in the degradation of diesel by a diesel-degrading bacterium. The isolate was tentatively identified as Acinetobacter sp. strain dry12 based on partial 16s rDNA molecular phylogeny and BiologÂ® GN microplate panels and MicrologÂ® database. Crude extract of the bacterium showed the presence of alkane-oxidizing, alcohol dehydrogenase and aldehyde dehydrogenase activities. The presence of these enzymes was further confirmed by the detection of 1-decanol, 1-decanal and 1-decanoic acid in the respective enzyme reaction mixtures. GC-MS fingerprint of several fatty acids detected in the growth media also suggested a terminal attack on diesel.
Keywords: diesel-degrading, Acinetobacter sp., terminal oxidation, alcohol dehydrogenase, aldehyde dehydrogenase; diesel-degrading; Acinetobacter sp.; Terminal Oxidation